Purification and biochemical characterization of a cyclodextrin glycosyltransferase from Geobacillus thermoglucosidans CHB1. (3rd July 2017) - Jia, Xianbo; Ye, Xuejun; Chen, Jichen; Lin, Xinjian; Vasseur, Liette; You, Minsheng
Abstract : A strain named Geobacillus thermoglucosidans CHB1 was isolated from stockpiled hen dung compost. The cyclodextrin glycosyltransferase (CGTase) from the fermentation broth of this microorganism was purified 350.50‐fold at a yield of 9.33% through ammonium sulfate precipitation, DEAE‐Sepharose Fast Flow chromatography, Sephadex G‐100 chromatography, and preparative electrophoresis. Sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) revealed that the molecular mass of the purified enzyme was approximately 70 kDa. The CGTase maintained more than 50% cyclization activity between 50 and 80°C and optimal activity at 65–70°C and remained stable at 50°C. Its optimal pH was 5.5, and its activity showed stability between pH 5.5 and 9.5. The activity of the enzyme was significantly enhanced by LiCl, NiCl2, and MgSO4 but inhibited by AlCl3, CoCl2, FeCl3, HgCl2, BaCl2, SDS, and ZnSO4 . The K m and V max of the reaction of this enzyme with soluble starch as the substrate were 12.5 mg/mL and 23.7 μmol/min, respectively. This enzyme produced α‐cyclodextrin (CD), β‐CD, and γ‐CD at a ratio of 0.57:1:0.21 from soluble starch as the substrate, and the conversion rate reached 60.3% from 3% soluble starch within 21 h. This CGTase also produced CDs from maltodextrin and potato starch as the substrate. To the best of our knowledge, this manuscript constitutes the first report of a CGTase purified from G. thermoglucosidans, and the results show that this enzyme might have potential for use in industrial production processes requiring stable thermal conditions, but further work is required to optimize its affinity and activation conditions.